ДОСЛІДЖЕННЯ ПЕРЕХІДНИХ ПРОЦЕСІВ В ЕЛЕКТРИЧНОМУ КОЛІ З СВІТЛОДІОДАМИ - Андрійчук, В.А.; Костик, Л.M.; Філюк, Я.O.; Наконечний, М.C. (Інститут електродинаміки НАН України, Київ, 2024)
The following documents presents the culmination of theoretical and innovative studies of transient processes in electric technology with a separate LED and their serial, parallel and varied connection.  It becomes apparent that the dynamics of current growth in a circuit with an LED has no significant changes when switching from a single LED to their parallel and series connection. Furthermore, the rise time of the current is much longer than the time of its fall. Comparing the dynamics of the current drop in the circuit and the voltage applied to the LED, is shown that they intersect. The suggested equivalent circuit of the LED, represented by the parallel link of the capacitor Cd and resistance Rd connected to the series resistance RS, is in good concurrent with theoretical calculations of transient processes and with the obtained innovative outcomes. The main task in the value of the time constant τ of the transient process is played by the capacitance of the capacitor Сd, which is ascertained by the diffuse capacitance of the heterojunction. Based upon obtained results, it was established that the maximum pulse power frequency of LED lighting devices is 8‧105 Hz. References 11, figures 5, table 1.